Antibacterial and cytotoxic secondary metabolites from endophytic fungi associated with Antidesma bunius leaves - Ni Putu Ariantari, I Putu Yogi Astara Putra, Ni Putu Eka Leliqia, Putu Sanna Yustiantara, Meitini Wahyuni Proborini, Nadzifa Nugraheni, Ummi Maryam Zulfin, Riris Istighfari Jenie, Edy Meiyanto (Journal of Applied Pharmaceutical Science, 2023)
Endophytic fungi isolated from Antidesma bunius leaves were investigated in this study. Six fungal endophytes were identified as Penicillium steckii AAB-01, Nemania bipapillata AAB-02, Xylaria feejeensis AAB-03, Hypomontagnella monticulosa AAB-04, Daldinia eschscholtzii AAB-05, and Phyllosticta capitalensis AAB-06. All of the isolated endophytic fungi were subjected to fermentation on rice media, followed by extraction with ethyl acetate. When tested for antibacterial activity, P. steckii AAB-01 extract showed the most potent inhibition against Staphylococcus aureus ATCC 6538 and Staphylococcus epidermidis ATCC 12228. Toxicity screening employing brine shrimp lethality test (BSLT) revealed potential toxicity of P. steckii AAB-01 and X. feejeensis AAB-03 extracts. Further investigation showed P. steckii AAB-01 extract had the highest inhibition toward MCF-7 cells, while D. eschscholtzii AAB-05 extract revealed the strongest cytotoxicity against 4T1 cells. Liquid chromatography-tandem mass spectrometry (LC-MS/MS) analysis tentatively identified five compounds, where indole acetic acid, O-acetylharmol, and oxindole I were suggested as the major metabolites in P. steckii AAB-01 extract, while 6-hydroxymelatonin and 2-methyl-6- pentadecylpyridine were suggested as the major metabolites in D. eschscholtzii AAB-05 extract. This is the first report on LC-MS/MS identification of the main metabolites from bioactive extracts of P. steckii AAB-01 and D. eschscholtzii AAB-05 isolated from the leaves of A. bunius, which might contribute to the antibacterial and cytotoxic properties of the extracts. Thus, a detailed investigation of antibacterial and cytotoxic metabolites from these endophytes merits further studies.